Transpor fronteiras: a circulação dos livros da editora mexicana Fondo de Cultura Económica no Brasil (1952–1965) - Bruna Marinho Valle Roriz (2022)
This dissertation examines the circulation of books from Mexican publisher Fondo de Cultura Económica (FCE) from 1952 to 1965 in Brazil. To achieve this, we examine FCE’s exclusive distributor in the country, Livraria Mestre Jou’s activities in promoting and distributing these books and developing a mediating position between the Mexican publisher and Brazilian intelligentsia. Publisher Fondo de Cultura Económica was established in 1934 with the purpose of providing Mexican students and scholars with access to foreign literature within the field of the humanities. In the 1940s, it began an expansion effort towards the Southern part of the continent, motivated both by commercial interests, as well as an overt intention of working for cultural integration of Latin America. Using publishing archives as our main sources – with special emphasis on business correspondence – we examine the challenges and dynamics of FCE’s book distribution in Brazil, traits of registered orders and returns, and the practices of cultural mediation that were developed in marketing these books. Throughout this work, we explore the mobilization of transnational bonds and cultural exchange involved in the network created between FCE and Mestre Jou. We’ve concluded that, in a context of increasing institutionalization of universities, the circulation of FCE’s books formed an important source of reading material for potential Brazilian consumers as it promoted access to highly-specific work translated into Spanish.